Epigenetic Regulation of Cell-Fate Changes That Determine Adult Liver Regeneration After Injury - Aloia, Luigi (Frontiers in Cell and Developmental Biology, 2021)
The adult liver has excellent regenerative potential following injury. In contrast to other organs of the body that have high cellular turnover during homeostasis (e.g. intestine, stomach and skin), the adult liver is a slowly self-renewing organ and does not contain a defined stem-cell compartment that maintains homeostasis. However, tissue damage induces significant proliferation across the liver and can trigger cell-fate changes, such as trans-differentiation and de-differentiation into liver progenitors, which contribute to efficient tissue regeneration and restoration of liver functions. Epigenetic mechanisms have been shown to regulate cell-fate decisions in both embryonic and adult tissues in response to environmental cues. Underlying their relevance in liver biology, expression levels and epigenetic activity of chromatin modifiers are often altered in chronic liver disease and liver cancer. In this review, I examine the role of several chromatin modifiers in the regulation of cell-fate changes that determine efficient adult liver epithelial regeneration in response to tissue injury in mouse models. Specifically, I focus on epigenetic mechanisms such as chromatin remodelling, DNA methylation and hydromethylation and histone methylation and deacetylation. Finally, I address how altered epigenetic mechanisms and the interplay between epigenetics and metabolism may contribute to initiation and progression of liver disease and cancer.